International management : - Hodgetts, Richard M. (McGraw-Hill, 2006)
As a discipline of academy inquiry, International Management applies management concepts and techniques to their contexts in firms working in multinational, multicultural environments. HodgettsLuthans: International Management was the first mainstream International Management text in the market. Its 6th edition continues to set the standard for International Management texts with its research-based content and its balance between culture, strategy, and behavior. International Management stresses the balanced approach and the synergy/connection between the texts four parts: Environment (3 chapters): Culture (4 chapters), Strategy and Functions (4 chapters) and Organizational Behavior /Human Resource Management (4 chapters)..